Strengthening the Traditional Markets: Evidence from Bosowasi Region, South Sulawesi - Syaparuddin Razak; Sari Utami; Jumriani Jumriani (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2020)
This research aimed to describe the model of strengthening the traditional markets. It was conducted in the Bosowasi region for six months. The type ofthis research was a qualitative descriptive one by using a social approach ingathering data and using the theory of social structure, social construction,social change, and planned behavior to analyze the data. The resultsof this research showed that (1) The modernization and technologicaldevelopment apparently do not necessarily eliminate people’s desire toshop in traditional markets, (2) The democratic trade model practiced intraditional markets can actually drive the people’s economy, and (3) Theinnovation, partnership and policies developed in traditional markets canmake them existing throughout time without compromising the needs offuture generations. These results served as the basis for formulating themodel of strengthening traditional markets and this model was called the“BSWS Model”. This model can make the traditional markets orderly, safe,clean and healthy, can make them competitive with the modern retailers,can improve services to the community, and can make them as a drivingwheel of the regional economy.